Herstories of alcohol and other drug use and imprisonment: understanding women's experiences of the Victorian correctional landscape, 1860-1920 - Groves, Andrew (Women's criminalisation and offending in Australia and New Zealand, 2024)
Much of the theory and knowledge used to inform research, policy, and crime prevention strategies regarding alcohol and other drugs (AODs) and their use is drawn from criminological research focused on the lives and experiences of men, as well as the criminal justice responses to their offending. Yet gender plays a crucial role in understanding historical and contemporary patterns of AOD-related offending and is central to novel theorising and application of strategies to address the enduring, putative ‘problem’ broadly conceived as substance misuse. This chapter examines imprisonment data from Victoria, Australia, between 1860 and 1920, looking backwards in moving forward to build knowledge of the nature and incidence of women being convicted and imprisoned for individual use, possession, and distribution-related drug and alcohol offences. This chapter details and discusses women’s experiences of their first interaction with the Victorian correctional landscape, including the differences in responses to female drug offending, and provides insights regarding the change in offending profiles from this significant period to contemporary contexts. This research reinforces the value of and need to examine women’s offending, alongside how criminal justice systems have responded to these women through incarceration. The findings demonstrate an inherently gendered and imbalanced historical approach to this form of crime and offending behaviour, underpinning the need for further criminological research that considers perspectives other than those of men.